Open Achilles Tendon Rerupture: A Case Report and Review of the Literature - Michael E. Doany; Megan C. Paulus (Case Reports in Orthopedics)
In this report, we describe a rare case of open rerupture of an Achilles tendon following primary surgical repair. The rerupture occurred 12 weeks postoperatively and was associated with a transverse open wound perpendicular to the original surgical incision. This complication was successfully managed utilizing the preexisting transverse wound and a minimally invasive repair technique, minimizing further risk to the soft tissues overlying the tendon. This rare complication has only been described a few times in the literature and is likely associated with adhesions between the tendon repair and the subcutaneous tissues.